Anti-politics: beyond supply-side versus demand-side explanations. Issue 4 (3rd December 2018) - Vines, Emma; Marsh, David
Abstract In the light of BREXIT and the election of Trump there has unsurprisingly been even greater interest in the rise in 'anti-politics'. We recognise anti-politics as an important, although not new, problem. The extant literature emphasiseeither demand-sideor supply-side explanations of the phenomena. In contrast, we argue that this involves a mis-specification of the problem, which neglects the interaction between the demand-side and the supply-side and, thus, leads to underdeveloped putative 'solutions'. Consequently, this article is structured around four questions that are at the core of any full discussion of anti-politics: What is 'anti-politics' and what are its consequences? Is it new? To the extent that it has increased, what are the causes of that increase? and What can be done about it? The empirical evidence we consider is drawn from the British case, both because much work has come out of the UK, and, relatedly, the problem appears especially acute there.